ADMINISTRATIVE AND FINANCIAL CHALLENGES ENCOUNTERED BY THE PUBLIC UNIVERSITIES IN SRI LANKA - Haththotuwa, Nishadhi (PEOPLE: International Journal of Social Sciences, 2017)
The heralding of the university system in Sri Lanka with a single university in 1942, currently comprises of 15 universities. The University Grants Commission being its pinnacle. Thus the university system in Sri Lanka continues to exist with all of the typical problems of a state owned monopoly. This paper will explore and critically review the pressing issues in public universities. Initially the literature review was used to examine the existing Higher Education System in Public Universities. Data is heavily drawn from the University Grants Commission’s statistical reports along with annual report data and tables published by various Public Universities and was statistically analysed using quantitative techniques. Attracting a pool of talented staff is a major issue seen in Public Universities. Offering low basic salaries hinders the advent of talented MBA/engineering degree holders whereas private sector rich with attractive salaries is in the forefront. Figures reveal that the percentages of those who left were more than those appointed in years 2011 and 2013 in the Administrative, Finance and Administrative Others category. The present management and administrative capacity of universities are comparatively underdeveloped in lagging regions. Sadly till 2013, there were no professors in the Uva Wellassa and South Eastern Universities.